Features of Material Flow Accounting for the Efficient Supply Chain Management - Vladimir B.Zotov; Sergey S.Demin; Irina Y.Glazkova (International Journal of Supply Chain Management, 2019)
Material flow accounting in supply chain management is a complex process for enterprises, regardless of industry and activities. Its use will enable companies to identify inefficiencies in the use of resources, as well as to assess the assets in terms of their durability, functionality, usefulness. Enterprises face many challenges in material flow accounting, and one of them is material flow accounting of stocks in the supply chain management. The organization has material losses in the absence of a coherent system of material flow accounting. The purpose of this study is to study the features of material flow accounting for the efficient supply chain management, to determine the effective systems of material flow accounting. We propose to use the MFCA system to account for material flow. It can be used to estimate material losses in the supply chain in terms of money and determine the economic benefits of resource efficiency. The MFCA methodology is regulated by the ISO standard. The article describes the process of material flow accounting at the studied enterprise in a specific example. It explains how to construct a methodological accounting framework to estimate resource losses from the economic point of view. We have systematized information on automated systems and programs for material flow accounting for the efficient supply chain management. A model of material flow accounting in accordance with ISO 14051 is developed and proposed for Alliance Oil Company. It is found that the production of gasoline produces a significant amount of by-products and waste. Only by-products, which are about 36 percent, are recorded under normal accounting. However, the use of MFCA has shown that most of the costs associated with material losses due to recycling products, waste, etc. In the study, we have compiled the matrix of material flow to Alliance Oil Company and found that the costs can be upgraded to material losses. In this case, they are $3930. $1130 is the estimated cost of electricity and the system cost of the refinery.